2008
DOI: 10.1021/es800876w
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Predictions of the Henry’s Law Constants and Their Temperature Dependence for the 209 Polychlorinated Biphenyl Congeners

Abstract: The Henry's law constants (HLCs) for all 209 polychlorinated biphenyl (PCB) congeners were predicted at 25 degrees C using the quantum mechanical (QM) continuum solvation models COSMO-SAC and SM6, and trends were examined. COSMO-SAC HLCs were also predicted for all congeners at 4, 11, 18, and 31 degrees C. The temperature dependences of the HLCs were used to calculate enthalpy of solvation (deltaHs) values. At 25 degrees C, COSMO-SAC and SM6 predicted similar values of the HLC, which are consistent with all bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The 1D RISM approach considers these effects in a proper way, even in the case of higher chlorinated compounds. In turn, the continuum solvent models (SM 6 and COSMO-SAC) 350 are not sensitive to the nonlinear solvent response (see Figure 19). These results illustrate that the 1D RISM/SDC(QMq) approach is a promising method that can be used to describe hydration/solvation processes for a wide range of chemical solutes.…”
Section: Molecule-surface Recognition and Supramolecular Interactionsmentioning
confidence: 99%
“…The 1D RISM approach considers these effects in a proper way, even in the case of higher chlorinated compounds. In turn, the continuum solvent models (SM 6 and COSMO-SAC) 350 are not sensitive to the nonlinear solvent response (see Figure 19). These results illustrate that the 1D RISM/SDC(QMq) approach is a promising method that can be used to describe hydration/solvation processes for a wide range of chemical solutes.…”
Section: Molecule-surface Recognition and Supramolecular Interactionsmentioning
confidence: 99%
“…However, accuracy of implicit solvent methods is often not enough for accurate prediction of the SFE; that is why in practice the methods with empirical corrections are often used. Many of methods of this type, such as COSMO-RS or SM6/SM8, allow one to calculate SFE with a high accuracy for some classes of simple compounds [9][10][11][12][13]. However, for the compounds with complicated structure these methods often fail to give a good correspondence to experiments [14,15].On the other hand, the numerical methods that have emerged in the second part of the last century from liquid-state theories [16,17], including integral equation theory in the reference interaction-site model (RISM) approximation [18][19][20][21][22][23] or in the molecular picture [24-26], classical density functional theory (DFT) [16, 27-29], or…”
mentioning
confidence: 99%
“…I soon found that to make reasonably accurate predictions, one needed accurate potentials of interactions between the molecules. The need for such information encouraged me to consider the application of quantum mechanical methods, for both the direct use of quantum mechanical methods in thermodynamics (86)(87)(88)(89)(90)(91)(92) and less direct methods in which quantum mechanics was first used to determine the electron distribution around molecules, and this information was used in applied thermodynamic models of mixtures (93)(94)(95)(96)(97)(98)(99)(100)(101)(102).…”
Section: Molecular Simulation and Quantum Mechanicsmentioning
confidence: 99%